P-033 YI Efficacy and Safety of Vedolizumab for Inflammatory Bowel Disease in Clinical Practice. (March 2016) - Chaudrey, Khadija; Lightner, Amy; Singh, Siddharth; Faubion, William; Tremaine, William; Bruining, David; Papadakis, Konstantinos; Kisiel, John; CoelhoPrabhu, Nayantara; Raffals, Laura; Kane, Sunanda; Loftus, Edward
Abstract : Background: Vedolizumab (VDZ) (Entyvio, Takeda Pharmaceuticals, Deerfield, IL) is a humanized monoclonal antibody to α4β7 integrin, resulting in gut-selective inhibition of lymphocyte trafficking. VDZ is approved for moderate to severely active ulcerative colitis (UC) and Crohn's disease (CD). The strict inclusion criteria and other constraints utilized in randomized control trials may limit the generalizability of efficacy and safety data in the GEMINI trials to "the real world." We sought to quantify the treatment effect and safety of VDZ in clinical practice at our institution. Methods: Institutional review board approval was obtained. UC and CD patients evaluated at Mayo Clinic, Rochester, Minnesota were included if they had: moderate to severely active UC or CD on baseline endoscopy within 4 weeks of starting VDZ (scored by an IBD specialist), active symptoms prior to starting VDZ, and clinical or endoscopic follow-up after induction. Outcomes included: physician global assessment (PGA), clinical response at induction and overall, steroid-free response and mucosal healing (Mayo endoscopic score of 0 or 1 for UC or healing of all ulcers and/or erosions for CD). Results: Retrospective chart review was performed for 91 patients on VDZ from August 2013 to August 2015. Sixty-three patients met inclusion criteria. Eighty percent of patients (n = 51) had CD while 20% (n = 12) had UC. During therapy with VDZ, patients with UC were more often on a concomitant steroid (66% versus 53%), while 17% of patients in both disease groups were on an immunomodulator. All UC patients had prior anti-tumor necrosis factor (TNF) failure, either due to lack of response or intolerance to the drug. Prior anti-TNF failure was comparably high (96%) for CD patients. PGA response rates for UC at induction were slightly higher compared to CD (66% versus 61%). Most patients with CD had a partial response, defined as 25% to 50% reduction in symptoms (58 for CD versus 36% for UC). Even though overall PGA response rates were higher for CD than UC (70% versus 58%), the majority of those patients with CD only had a partial response (49% for CD versus 25% for UC). Thirty-three patients underwent an assessment for mucosal healing, which was successfully achieved in 8 (24%) of these patients. Amongst the patients assessed for mucosal healing, the percentage of patients who achieved mucosal healing was higher within the UC group versus CD (66% versus 20%). Five patients included in the study group developed an infection. Most required no antibiotic therapy or outpatient antibiotic management only. Rates of progression to surgery were higher for UC versus CD (25% versus16%). No new safety signal was identified. Conclusions: In this interim analysis of a relatively refractory patient cohort, UC patients achieved higher PGA induction response and mucosal healing rates with VDZ than CD. This may be related to differences in disease characteristics or practice variations when utilizing VDZ.